La cerámica común Romana en la bahía Gaditana en época Romana : alfarerîa y centros de producciôn - Anguiozar, Lourdes Girón, (Archaeopress Roman archaeology ;, 2017)
This volumes examines Roman pottery and production centres in the bay of Gaditana, modern-day Cádiz.